siRNA Targeting PDE5A Partially Restores Vascular Damage Due to Type 1 Diabetes in a Streptozotocin-Induced Rat Model - Vanessa Giselle Garcia-Rubio; Sandra Edith Cabrera-Becerra; Sergio Adrian Ocampo-Ortega; Citlali Margarita Blancas-Napoles; Vivany Maydel Sierra-Sánchez; Rodrigo Romero-Nava; Rocío Alejandra Gutiérrez-Rojas; Fengyang Huang; Enrique Hong; Santiago Villafaña (Scientia Pharmaceutica, 2023)
Diabetes mellitus is a metabolic disease that can produce different alterations such as endothelial dysfunction, which is defined as a decrease in the vasodilator responses of the mechanisms involved such as the nitric oxide (NO) pathway. The overexpression of PDE5A has been reported in diabetes, which causes an increase in the hydrolysis of cGMP and a decrease in the NO pathway. For this reason, the aim of this study was to evaluate whether siRNAs targeting PDE5A can reduce the endothelial dysfunction associated with diabetes. We used male Wistar rats (200–250 g) that were administered streptozotocin (STZ) (60 mg/kg i.p) to induce diabetes. Two weeks after STZ administration, the siRNAs or vehicle were administered and then, at 4 weeks, dose–response curves to acetylcholine were performed and PDE5A mRNA levels were measured by RT-PCR. siRNAs were designed by the bioinformatic analysis of human–rat FASTA sequences and synthesised in the Mermade-8 equipment. Our results showed that 4 weeks of diabetes produces a decrease in the vasodilator responses to acetylcholine and an increase in the expression of PDE5A mRNA, while the administration of siRNAs partially restores the vasodilator response and decreases PDE5A expression. We conclude that the administration of siRNAs targeting PDE5A partially reverts the endothelial impairment associated with diabetes.